High-Intensity Focused Electromagnetic Field With Synchronized Radiofrequency Achieves Superior Gluteal Muscle Contouring Than High-Intensity Focused Electromagnetic Field Procedure Alone. (10th January 2023) - DiBernardo, Barry; Chilukuri, Suneel; McCoy, J D; Katz, Bruce; Goldberg, David J
Abstract: Background: The high-intensity focused electromagnetic field (HIFEM) procedure is an effective method for noninvasive toning and shaping of buttocks. Objectives: To investigate and compare the efficacy of simultaneous application of HIFEM procedure with radiofrequency (RF) heating vs HIFEM standalone procedure on the buttocks. Methods: Sixty-seven subjects (21-67 years, BMI 16-34 kg/m 2 ) were recruited and divided into two groups. Group A received simultaneous HIFEM + RF therapy, and group B received standalone HIFEM treatments. All participants underwent four 30-minute bilateral treatments on the buttocks. The MRI was used to evaluate the changes in muscle and fat thickness. Results: Data of 32 subjects from group A and 31 subjects from group B were reviewed at 1-month follow-up. On average, subjects from group A showed a 31.3% higher increase in muscle thickness, as shown in the MRI evaluation. The gluteal muscle thickness continued to grow and peaked at a 3-month follow-up, wherein 27 patients were evaluated in each group ( n = 54). Group A showed on average +24.7% increase (gluteus maximus +8.5 ± 1.9 mm, medius +6.0 ± 1.1 mm, minimus +2.9 ± 0.8 mm), while group B exhibited only +15.9% increase in muscle thickness (gluteus maximus +5.2 ± 1.1 mm, medius +3.6 ± 1.0 mm, minimus +1.6 ± 0.4 mm). On average, group A showed a 35.6% higher growth in muscle thickness. Treatments were safe and comfortable with high satisfaction rates. No adverse event was reported throughout the study. Conclusions: Our results suggest that simultaneous use of HIFEM + RF is safe and significantly more effective for gluteal contouring than the HIFEM procedure alone. Level of Evidence: 2: